Penerapan Model Pembelajaran Kooperatife Tipe Think Pair Share (TPS) Pada Meteri Tata Nama Senyawa Terhadap Peningkatan Hasil Belajar Siswa Kelas X SMA Negeri 1 Bahodopi - Marwina Marwina; Sitti Aminah (Universitas Tadulako, 2022)
This study was conducted to describe the increase in student learning outcomes after the application of the Think Pair Share (TPS) cooperative learning model in Class X Compound Nomenclature at SMA Negeri 1 Bahodopi. This type of research is a Pre-Experimen research with one group Pre-test and Post-test design. The population in this study were all students of class X MIA at SMA Negeri 1 Bahodopi which consisted of three classes, namely class X MIA 1, MIA 2, and X MIA 3 with a total of 91 students. The sample in this study were 30 students of class X MIA 3 as Experiment class 1 and students of class X MIA 1 as many as 30 people as experiment class 2. The sampling technique used was purposive sampling. The instrument of this research is a test of learning outcomes. In the replication class 1, the student's learning outcomes were 75.83, while the replication class 2 was 76.83. The research data obtained from the two classes were analyzed using the N-Gain test, which was used to determine the increase in student learning outcomes. The data from the N-Gain test was obtained in the replication class 1 which was an average of 0.62 and the replication class 2 was an average of 0.63. The results of the data from the N-Gain test obtained that g = value 0.30 (<g>) <0.70 was in the medium category, which indicated that there was a change in student learning outcomes after the application of the Think Pair Share (TPS) cooperative learning model.